THE INFLUENCE OF TIKTOK DA'WAH CONTENT AND PARENTAL SUPERVISION ON THE CHARACTER OF MUSLIM ADOLESCENTS IN MEDAN CITY - Muhammad Imam Nawawi Rangkuti; Ali Imran Sinaga; Muhammad Al Farabi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The rapid growth of social media has transformed the dissemination of Islamic preaching while simultaneously influencing the character development of Muslim adolescents. As one of the most widely used digital platforms among young people, TikTok has the potential to serve as an effective medium for Islamic preaching, although its effectiveness is closely associated with parental supervision. This study aims to examine the influence of TikTok da'wah content and parental supervision on the character of Muslim adolescents in Medan City, both partially and simultaneously. A quantitative survey design was employed involving 100 Muslim adolescents who actively use TikTok, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination analysis. The findings indicate that TikTok da'wah content has a positive and significant effect on Muslim adolescents' character (β = 0.483; p < 0.001). Likewise, parental supervision also demonstrates a positive and significant influence (β = 0.232; p = 0.003). Simultaneously, both variables significantly affect Muslim adolescents' character (F = 40.195; p < 0.001), with a coefficient of determination (R²) of 0.453. These findings suggest that character development among Muslim adolescents in the digital era is shaped by the synergy between high-quality digital da'wah content and effective parental supervision. This study contributes to the literature on digital da'wah and Islamic character education by emphasizing the importance of collaboration among families, educators, and digital content creators in fostering an educational digital ecosystem that strengthens the character of the younger generation.